Arrested development of experimental Cyathostominae infections in ponies in Czech republic - Scháňková, Štěpánka; Maršálek, Miroslav; Wagnerová, Pavla; Langrová, Iva; Starostová, Lucie; Stupka, Roman; Navrátil, Jan; Brožová, Adéla; Truněčková, Jana; Kudrnáčová, Marie; Jankovská, Ivana; Vadlejch, Jaroslav; et al. (Veterinary parasitology, 2014)
Nine ponies, aged 12 months at the time of infection, were randomly allocated to one of three groups. Each pony was infected with 30,000 infective cyathostome larvae stored 4 weeks under the natural environmental conditions of the Czech Republic. Horses of Group A were infected with larvae conditioned from August 16 to September 12 (the first phase of the experiment). Horses of Group B were inoculated with larvae conditioned from October 10 to November 4 (the second phase of the experiment). In the third phase, horses from Group C received larvae stored under natural conditions (from 8.11 to 18.11.2011). The larvae were then kept under laboratory conditions (5 °C, the light reduction according to the nature condition). In the first and second phase of the experiment, 98.57% and 95.48% of adult nematodes were found, respectively. However, only 29.07% of adults were found in the third phase of experiment, and the proportion of arrested larvae (EL3) was 67.73%. The share of these larvae in the cecum during last phase of the experiment comprised 92.59% of all cyathostomes.
Keywords: strongyloidóza koní; nemoci koní; Strongyloidea; Česká republika; Animals; Horse Diseases; Horses; Random Allocation; Larva; zvířata; Strongyle Infections, Equine; cékum; Cecum; Czech Republic; náhodné rozdělení; larva; koně